Minho robotic football team - Machado, Carlos (2000)
Autonomous mobile robots are ever increasing their number of different applications, even in ludic applications or in sports. In the last few years, several robotic football competitions have been organized with participating teams from all over the world. This paper describes a team of Autonomous Mobile Robots which play football, developed by the Group of Automation and Robotics at the Industrial Electronics department (School of Engineering) of the University of Minho, in Guimarães (Portugal). In these competitions each team is free to use and/or build all the different electronics, sensory systems, playing algorithms, etc. as far as they cope with the rules imposed by the organization. From every team new ideas emerge, sometimes the most incredible ones, but proving in the end that they work. These competitions proved to be very fruitful scientifically as well as very mediatic.